Developing English for Maritime Coursebook through Project-Based Concern: Aligning with Seafarers' STSDD Certification Requirements - Ahmad Nusi; M Zaim; Havid Ardi (Universitas Syiah Kuala, 2025)
This study investigates the implementation of project-based concern to develop an English coursebook model for maritime training aligned with Seafarers' STSDD certification requirements. Following Gall Borg model design, the research obviously aimed to create an interactive teaching material model suitable for a foundational English course tailored for seafarers. Educational needs were identified through surveys, interviews, and documentation, revealing ten thematic areas structured with five tasks each. These thematic areas encompassed essential topics such as maritime communication, safety procedures, navigation, marine engineering, cargo operations, environmental awareness, cultural competence, legal aspects, health, and emergencies. Tasks within these areas included theoretical knowledge, in-class exercises, and practical field assignments designed to enhance both individual and group learning experiences. These components were meticulously aligned with standards aimed at improving English for Maritime language skills among seafarers preparing for STSDD certification. The resulting teaching material model project-based concern tailored guidelines specific to the unique contexts of maritime training. Effectiveness was assessed using the N-Gain Score, resulting in a score of 0.86 (86.36%), indicating a significant enhancement in language skills. The findings suggest that this project-based concern not only improves seafarers English for Maritime language skills but also holds practical implications for onboard application. By incorporating project-based concern and specific materials, educators can optimize training programs to better equip seafarers for the linguistic demands of their roles and the requirements of STSDD certification exams.